Precipitation behavior (1918/2000) in west central Buenos Aires province (Argentina) (Semiárida, 2020)
During the last decades, the western center of the province of Buenos Aires registered a significant increase of the grain cultivation area due to the increase of the demand of cereals and oil crops and to the technological innovations. There are indications which show that that process was favored by the increase in the precipitations which started in the beginings of the 60. From this, a study of the changes of the precipitations in the area was carried out, with the purpose to evaluate its influence in the process. In the evaluated period (1918/2000), it could be verified that, according to the indicated works oi investigation made previously, the region presented a cycle of long duration with damp and dry phases, separated by phases of transition, that extended approximately during the following periods: 1} End of a phase of transition wet/dry between the beginning of the period evaluated and the mid 20s; 2) Dry phase between the mid 20s and the late 40s; 3) Phase of transition dry/wet between the early 50s and the 70s; 4) wet phase between the mid 70s and the late 90s. To be a strip of transition between the damp climate of the Eastern region and the semi-arid climate that extends towards the west of Argentina, the area presents a high vulnerability to the fluctuations of the rain regime, therefore it is necessary to anticipate the consequences that would bring entailed the return to periods of low precipitations. It must be considered the importance of developing technological resources that allow to surpass a possible diminution of rains during the next decades.
Keywords: Cycle; precipitation; Western Center of Buenos Aires